2014
DOI: 10.1080/09712119.2013.875905
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of selected performance indicators, nutrient digestibility and nitrogen balance parameters in Californian and Flemish Giant rabbits

Abstract: Medium rabbit breeds such as Californian (CAL) are generally regarded as most suitable for meat production on commercial farms. Despite the increasing scale of production, commercial rabbit breeding has not replaced traditional and organic small-scale farming systems which use various rabbit breeds and hybrids. The Flemish Giant (FG), the largest rabbit breed in the world, is widely used in small household farms. According to researchers, the progeny of FG does have a relatively high weaning weight, and bucks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
(13 reference statements)
1
7
3
Order By: Relevance
“…The performance parameters of rabbits from all groups (Table 4) were within normal limits for growing meat-type rabbits of medium-sized breeds raised in Europe [5,27,32]. However, only a few studies have investigated the efficacy of Sida hermaphrodita in livestock nutrition, and there appears to be no published information on rabbits.…”
Section: Discussionmentioning
confidence: 93%
“…The performance parameters of rabbits from all groups (Table 4) were within normal limits for growing meat-type rabbits of medium-sized breeds raised in Europe [5,27,32]. However, only a few studies have investigated the efficacy of Sida hermaphrodita in livestock nutrition, and there appears to be no published information on rabbits.…”
Section: Discussionmentioning
confidence: 93%
“…Noteworthy is also a higher content of lysine in SBM (2.64%) than in RSC (1.95%) and wheat DDGS (barely 0.77%). Our recent research (Strychalski et al 2014) demonstrated that BWG of these rabbits were much lower compared with Flemish Giant rabbits. In finished feed mixtures (Table 2), the content of crude protein ranged from 15.6% to 16.8%, which met the protein requirement of 15.3% for growing rabbits (Carabaño et al 2009).…”
Section: Experimental Dietsmentioning
confidence: 91%
“…Carcass characteristics and meat quality are the fundamental aspects that guide research on the production of fattening rabbits, due to the relevance reached by this species to produce meat of good nutritional quality (Dalle Zotte 2002;Dal Bosco et al 2012;Capra et al 2013) with high reproductive and growing performance (Strychalski et al 2014). Rabbit meat has several attributes that make it superior to that of other species, mainly its higher protein and lower fat contents (Dalle Zotte 2002).…”
Section: Introductionmentioning
confidence: 99%